Proteasome targeting of proteins in Arabidopsis leaf mesophyll, epidermal and vascular tissues - Svozil, Julia; Gruissem, Wilhelm; Baerenfaller, Katja (Frontiers in Plant Science, 2015)
Protein and transcript levels are partly decoupled as a function of translation efficiency and protein degradation. Selective protein degradation via the Ubiquitin-26S proteasome system (UPS) ensures protein homeostasis and facilitates adjustment of protein abundance during changing environmental conditions. Since individual leaf tissues have specialized functions, their protein composition is different and hence also protein level regulation is expected to differ. To understand UPS function in a tissue-specific context we developed a method termed Meselect to effectively and rapidly separate Arabidopsis thaliana leaf epidermal, vascular and mesophyll tissues. Epidermal and vascular tissue cells are separated mechanically, while mesophyll cells are obtained after rapid protoplasting. The high yield of proteins was sufficient for tissue-specific proteome analyses after inhibition of the proteasome with the specific inhibitor Syringolin A (SylA) and affinity enrichment of ubiquitylated proteins. SylA treatment of leaves resulted in the accumulation of 225 proteins and identification of 519 ubiquitylated proteins. Proteins that were exclusively identified in the three different tissue types are consistent with specific cellular functions. Mesophyll cell proteins were enriched for plastid membrane translocation complexes as targets of the UPS. Epidermis enzymes of the TCA cycle and cell wall biosynthesis specifically accumulated after proteasome inhibition, and in the vascular tissue several enzymes involved in glucosinolate biosynthesis were found to be ubiquitylated. Our results demonstrate that protein level changes and UPS protein targets are characteristic of the individual leaf tissues and that the proteasome is relevant for tissue-specific functions.